Severe dysphagia due to rapidly progressive pharyngoesophageal segment stenosis in systemic sclerosis. Issue 3 (September 2016) - Jeffery, Caroline C.; Jung, Michelle
Purpose: To describe a case of pharyngo-esophageal segment involvement by systemic sclerosis resulting in severe and rapid progressive dysphagia refractory to management. Case report: A 69-year-old female with known systemic sclerosis presented with progressive solid and liquid food dysphagia. Serial video fluoroscopic swallowing studies demonstrated progressive hypopharyngeal and upper esophageal sphincter stenosis along with oropharyngeal dysphagia. Attempted esophagogastroduodenoscopy by gastroenterology using a 5.4 mm diameter gastroscope failed to pass through the hypopharynx. Operative laryngoscopy demonstrated a 3 mm hypopharyngeal lumen extending for 2 cm into the cervical esophagus. The stenosis was cannulated and dilated to 10 mm, but remained refractory to further dilations. The patient was unable to maintain any oral intake and required percutaneous gastrostomy placement. Conclusions: Involvement of the pharyngo-esophageal segment is an underreported cause of severe dysphagia in patients with systemic sclerosis. Early recognition is necessary to prevent complete stenosis.